2013
DOI: 10.7150/ijms.5798
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Immune Cells: Triggers for Tumor Capsule Disruption and Tumor Progression?

Abstract: Background: Our previous studies of human breast and prostate cancer have shown that aberrant immune cell infiltration is associated with focal tumor capsule disruption and tumor cell budding that facilitate invasion and metastasis. Our current study attempted to determine whether aberrant immune cell infiltration would have similar impact on colorectal cancer (CRC).Materials and Methods: Tissue sections from 100 patients with primary CRC were assessed for the frequencies of focal basement membrane (BM) disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…In their comparative study of DCIS, microinvasive carcinomas and T1a cancers, Mori et al 8 demonstrated a higher rate of HER2 positivity in microinvasive carcinoma similar to the present study and formulated the hypothesis that ‘HER2 plays an important role in making the first invasion.’ Based on the five characteristics mentioned above, we propose two possible explanations for the higher HER2 positivity rate in microinvasive carcinoma: first, that HER2-positive cancers are likely to be detected at breast cancer screenings using mammography because they have large comedo; second, that due to its strong immunogenicity, HER2 causes increased accumulation of TIL especially CD8+ cytotoxic T lymphocytes already in the in situ stage and that a disruption of the myoepithelium and basement membrane occurs during the stage of healing, so that cancer cells are exposed in the stroma as a cluster-like invasion. In a study on colorectal cancer, Jiang et al reported that TIL is involved in the focal disruption of tumour 24. Chivukula et al 13 reported that the presence of myoepithelium was confirmed in only 91% of cases of high-grade DCIS with regressive changes, which suggests that TIL may be involved in elimination of tumour and also in the disruption of the epithelium and the resulting formation of microinvasive foci in early breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In their comparative study of DCIS, microinvasive carcinomas and T1a cancers, Mori et al 8 demonstrated a higher rate of HER2 positivity in microinvasive carcinoma similar to the present study and formulated the hypothesis that ‘HER2 plays an important role in making the first invasion.’ Based on the five characteristics mentioned above, we propose two possible explanations for the higher HER2 positivity rate in microinvasive carcinoma: first, that HER2-positive cancers are likely to be detected at breast cancer screenings using mammography because they have large comedo; second, that due to its strong immunogenicity, HER2 causes increased accumulation of TIL especially CD8+ cytotoxic T lymphocytes already in the in situ stage and that a disruption of the myoepithelium and basement membrane occurs during the stage of healing, so that cancer cells are exposed in the stroma as a cluster-like invasion. In a study on colorectal cancer, Jiang et al reported that TIL is involved in the focal disruption of tumour 24. Chivukula et al 13 reported that the presence of myoepithelium was confirmed in only 91% of cases of high-grade DCIS with regressive changes, which suggests that TIL may be involved in elimination of tumour and also in the disruption of the epithelium and the resulting formation of microinvasive foci in early breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that tumor-infi ltrating immune cells disrupt intercellular junctions and cell-surface adhesion molecules of cancer cells, thereby causing destruction of the tumor capsule and activation of tumor dissemination. 43,44 In particular, it has been reported that tumorassociated macrophages were found at signifi cant concentrations within the region of tumor budding at the tumor invasive front 22 and that they promoted cancer cell invasiveness via epithelial mesenchymal transition. [23][24][25] Figure We did not perform colocalization studies on the same slide using immunofl uorescent techniques, which was a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that NK cells may be conditioned or anergized by other immune effectors or the effectors of connective tissue to support differentiation of the epithelial layer. In cancer, NK cells may obtain entry to the tumor site after the myoepithelial layer forming the tumor capsule is disrupted (Jiang et al, 2013a, b;Man et al, 2013). As such, any NK cells that have escaped from the binding and anergizing effects of MDSC may be able to lyse some of the tumor stem cells, in addition to inducing differentiation in a fraction of the tumor cells (Figures 1c-e).…”
Section: Cd56mentioning
confidence: 99%
“…Therefore, these results suggested that receptor signaling in NK cells via key surface receptors in the presence of IL-2 is likely to result in a rapid loss of NK cell cytotoxicity while continuing to increase secretion of cytokines by the NK cells. (Jiang et al, 2013a, b;Man et al, 2013). Although some NK cells may be found in the tumor nests, it appears that most cells are seen in the immune compartment associated with other immune effectors such as mast cells (Figure 1).…”
Section: Cd56mentioning
confidence: 99%